Chemical composition of the Essential Oil Extracted from aerial parts of Pistacia Atlantica in Safita region-Tartous-Syria - Hwije , Emad; Alboudi , Hasan; Dagher, Sandy (Latakia University Journal -Basic Sciences Series, 2018)
Chemical composition of the essential oil extracted by hydrodistillation (Clevenger apparatus) from some aerial parts (ripe and unripe fruit) of Pistacia Atlantica (Anacardiaceae) which are widely spread throughout the countries of the Mediterranean Sea and have been occupying a good part of the mount of Syria was determined by Gas Chromatography-Mass Spectrometer GC/MS. The results of analyzing showed that the oil consist of five compounds in ripe and unripe fruit, and it was found that the component with the highest ratio in both samples is the same 2-methylbutanal and its ratio 95.713% in the ripe fruit and 94.138% in the unripe fruit. The results of this study also show that the essential oil components of the Syrian Pistacia fruits are completely different from those in different environments due to the different types of pistacia species which have been studied and the different environmental conditions in which this plant grows.